Surgical Correction of Popliteal Pterygium with Serial Splinting: A Case Report and Review of Literature - Mohammed Sewilam, MD (Wolters Kluwer, 2021)
Summary:. Popliteal pterygium syndrome is an extremely rare congenital disorder, with only a few cases reported in the literature. It consists of facial, genitourinary, and musculoskeletal anomalies. A very striking characteristic of this syndrome is the popliteal pterygium contracture, which is considered the most challenging malformation to be corrected. Hence, we report a case of popliteal pterygium contracture in a 30-month-old female child with no family history of popliteal pterygium syndrome. The child was treated successfully with satisfactory results, by combining surgical intervention with postoperative serial splinting. We discuss here the tips and tricks of the surgical approach we performed, which was followed by serial splinting and physiotherapy. In addition, a literature-based review was performed providing a summary of all relevant reported cases.